(untitled) (Scientific journal of the Fergana State University, 2024)
The article describes the harmonious aspects of human life with nature and social events, and the reflection of this harmony in fiction. The gradual improvement of the image of the bird as a result of the development of socio-philosophical thinking is discussed.